Legal Analysis of the Mass Corruption Phenomenon of Board Members and Criminal Liability - Simatupang, Jonasmer (Law Research Review Quarterly, 2019)
The Republic of Indonesia unitary state ia a legal state based on the constitution. In a country that adheres to democracy, the law become the supreme commander in a effort to eradicate criminal cases and included acts of corruption corruption crime in Indonesia is a social issues that has never been exhausted to be discussed, in the world of law, this has been included in the category of extradionary crime because is not only harms the state, but the practice also violates the social and economic rights of the community a large so that eradication action must also be carried out with extradionary legal force. A pattern or phenomena of bulk corruption is recently revealed by the people’s deputy officials. Almost the world room of the representative of the people of good people at the local people until the center was ever searched and representative of the people were brought to committing corruption in a way of like a budget, received a bribe and so forth. The practice has occured in the area of North Sumatera and city Malang. Various of these cases made the reputation of the people’s institutions deterioting among the people. Through this writing by analizing and investigating more deeply technical and systematic practice of the board members in the distorting the budget.